Prostate‐specific antigen screening impacts on biochemical recurrence in patients with clinically localized prostate cancer. (6th April 2018) - Hashimoto, Takeshi; Ohori, Makoto; Shimodaira, Kenji; Kaburaki, Naoto; Hirasawa, Yosuke; Satake, Naoya; Gondo, Tatsuo; Nakagami, Yoshihiro; Namiki, Kazunori; Ohno, Yoshio
Abstract : Objective: To clarify the impact of prostate‐specific antigen screening on surgical outcomes of prostate cancer. Methods: Patients who underwent radical prostatectomy were divided into two groups according to prostate‐specific antigen testing opportunity (group 1, prostate‐specific antigen screening; group 2, non‐prostate‐specific antigen screening). Perioperative clinical characteristics were compared using the Wilcoxon rank‐sum and χ 2 ‐tests. Cox proportional hazards models were used to identify independent predictors of postoperative biochemical recurrence‐free survival. Results: In total, 798 patients (63.2%) and 464 patients (36.8%) were categorized into groups 1 and 2, respectively. Group 2 patients were more likely to have a higher prostate‐specific antigen level and age at diagnosis and larger prostate volume. Clinical T stage, percentage of positive cores and pathological Gleason score did not differ between the groups. The 5‐year biochemical recurrence‐free survival rate was 83.9% for group 1 and 71.0% for group 2 ( P  < 0.001). On multivariate analysis, prostate‐specific antigen testing opportunity (hazard ratio 2.530; P  < 0.001) was an independent predictive factor for biochemical recurrence after surgery, as well as pathological T stage, pathological Gleason score, positive surgical margin and lymphovascular invasion. Additional analyses showed that prostate‐specific antigen screening had a greater impact on biochemical recurrence in a younger patients, patients with a high prostate‐specific antigen level, large prostate volume and D'Amico high risk, and patients meeting the exclusion criteria of the Prostate Cancer Research International Active Surveillance study. Conclusions: Detection by screening results in favorable outcomes after surgery. Prostate‐specific antigen screening might contribute to reducing biochemical recurrence in patients with localized prostate cancer.